Yuma: Geração de Workflows Multiagentes a partir de Linguagem Natural - Neves, André; Mantovani, Daniel; Campelo, Caíque; Souza, Gabriel; Souza, Débora; Furtado, Beatriz; Balby, Leandro; Araújo, Eliane (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Large Language Models (LLMs) have enabled the translation of natural language into functional systems. However, creating multiagent systems based on these models still requires advanced technical knowledge. In this work, we present Yuma, a multi-agent tool that simulates software engineering roles — Requirements Engineer and Software Architect — to collaboratively generate multi-agent systems. This approach translates users’ informal requirements into deployable workflows, with human supervision at each step, ensuring transparency and validation. The tool coordinates requirements elicitation, architecture definition, and system generation, reducing the technical barrier to creating solutions. Finally, we present the tool’s architecture, the interaction flow, and a usage example, demonstrating how this approach democratizes access to multi-agent technologies, making them accessible and transparent to non-specialized users.